2010
DOI: 10.1007/s00705-010-0825-7
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of pandemic 2009 influenza A virus circulating in the South American region: genetic relationships and vaccine strain match

Abstract: The first influenza pandemic of this century was declared in April of 2009, with the emergence of a novel H1N1 influenza A virus strain (H1N1pdm). Understanding the evolution of H1N1pdm strains within the South American region is essential for studying global diversification, emergence and resistance, as well as determining vaccine efficacy. In order to gain insight into these matters, phylogenetic analysis was performed using 29 hemagglutinin (HA) gene sequences from H1N1pdm strains isolated in South America.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Phylogenetic analysis of the HA 1 gene from 2009A/H1N1 isolates from Kashmir revealed similarities to 2009A/H1N1 clade 7. This is in agreement with recent results obtained in other parts of the world, where clade 7 was the most commonly detected clade, although cocirculation of clades 5, 6, and 7 has been observed in some parts of the world 16–18 . Amino acid substitutions in the HA protein characteristic for clade 7 (P83S, S203T and I321V) were identified in all Srinagar isolates, with two exception where I321I was present in two of the isolates.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Phylogenetic analysis of the HA 1 gene from 2009A/H1N1 isolates from Kashmir revealed similarities to 2009A/H1N1 clade 7. This is in agreement with recent results obtained in other parts of the world, where clade 7 was the most commonly detected clade, although cocirculation of clades 5, 6, and 7 has been observed in some parts of the world 16–18 . Amino acid substitutions in the HA protein characteristic for clade 7 (P83S, S203T and I321V) were identified in all Srinagar isolates, with two exception where I321I was present in two of the isolates.…”
Section: Discussionsupporting
confidence: 92%
“…Few of the strains from Srinagar clustered with the Asian strains, with A/India‐Srinagar/3/2010 showing similarities to (A/Quebec/144147/2009); A/India‐Srinagar/4/2010 and A/India‐Srinagar/7/2010 showing similarities to (A/EHIME/33/2010), and A/India‐Srinagar/1/2010, A/India‐Srinagar/2/2010, and A/India‐Srinagar/6/2010 showing similarities to (A/Daegu/1873/2009) (Figure 2). Unlike cocirculation of clades 5, 6, and 7, in some parts of India and South America, 16,18 all isolates from Srinagar clustered in clade 7 (Figure 2).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…6 The Ca1 antigenic site in the majority of the Lebanese isolates had an S206T mutation, which has been reported as a characteristic mutation of a widespread H1N1 pdm strain. [13][14][15] We showed that this strain also had 2 amino acid mutations in NA: V42I and N248D. The phylogenetic history of these viruses suggested that these NA mutations evolved prior to the HA S206T mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences from the HA segment reproduce the phylogenetic topology for, the presumably more virulent, clade 6 and 7 viruses [17]. In South America, viruses from clades 5, 6 and 7 co-circulated [21]. Polymorphisms found in clade 6 strains have been identified and include the K-15E, P83S and Q293H mutations (ESH strain) [5,[13][14][15]17].…”
Section: Introductionmentioning
confidence: 78%